An insight into the sialome, mialome and virome of the horn fly, Haematobia irritans - Ribeiro, J.M.; Debat, Humberto Julio; Boiani, M.; Ures, X.; Rocha, S.; Breijo, M. (BMC, 2019)
Background: The horn fly (Haematobia irritans) is an obligate blood feeder that causes considerable economic losses in livestock industries worldwide. The control of this cattle pest is mainly based on insecticides; unfortunately, in many regions, horn flies have developed resistance. Vaccines or biological control have been proposed as alternative control methods, but the available information about the biology or physiology of this parasite is rather scarce. Results: We present a comprehensive description of the salivary and midgut transcriptomes of the horn fly (Haematobia irritans), using deep sequencing achieved by the Illumina protocol, as well as exploring the virome of this fly. Comparison of the two transcriptomes allow for identification of uniquely salivary or uniquely midgut transcripts, as identified by statistically differential transcript expression at a level of 16 x or more. In addition, we provide genomic highlights and phylogenetic insights of Haematobia irritans Nora virus and present evidence of a novel densovirus, both associated to midgut libraries of H. irritans.